STRATEGI PEMASARAN AIR MINUM DALAM KEMASAN PT. AFRESH JAMBI - , Raden Roro Herawaty Diah Adriani, Dr. Ir. Lestari Rahayu Waluyati, MP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze the internal environment and external from PT. AFRESH Jambi is to determine what factors are the strengths and weaknesses of the enterprise and identify opportunities and threats faced by the company and formulate the best marketing strategies and suitable for PT. AFRESH Jambi taking into account internal factors (strengths and weaknesses)and external factors (threats and opportunities) to face competition and environmental chages on the bottle water industry. Strength PT. AFRESH Jambi is a Research and Development, Brand Image, Employee Loyalty, Distribution Chanels, Cost of goods sold, Quality Human Resources, Experience in The Production and Marketing, Management Capabilities that are Reliable in The Face Competition, Quality of Product. The Weaknesses are the Availiability of Raw Materials and Product Costs. Opportunities PT. AFRESH Jambi in Market Segmen, Market Growth, Responses to Promotions, Prices of Competing Product, Product Development. The Threat is Competition Bottled Water Products in The Other, Government Policies, Changes in Consumer Taste, Entry of New Copetitors, Price Competition. The position PT. AFRESH Jambi in quadrant I with a larger area of greater strength than its weakness also had a greater opportunity than a threat, so the company should be able to use force to take advantage of opportunities. Companies must implement aggressive marketing strategies sufficient to maintain competition in the bottled water industry.